Recruitment of Three Generations of African American Women Into Genetics Research - Taylor, Jacquelyn Y. (2009)
Successful outcomes for studies on health disparities depend on recruitment of research participants. Obtaining willing participants, protecting their rights, and acknowledging their contribution to research is as important as seeking answers to the study phenomena. Recruiting research participants can be an arduous process for investigators. Although literature has published participant recruitment methods, investigators sometimes underestimate the time and intensity required to attract eligible participants into research studies. This article reports on methods used to recruit 42 African American generational triads (grandmothers, mothers, and granddaughters) into a hypertension genetics study, the lessons learned, and suggestions for successful recruitment.